2017
DOI: 10.1038/nchem.2856
|View full text |Cite
|
Sign up to set email alerts
|

Vibronically coherent ultrafast triplet-pair formation and subsequent thermally activated dissociation control efficient endothermic singlet fission

Abstract: Singlet exciton fission (SF), the conversion of one spin-singlet exciton (S) into two spin-triplet excitons (T), could provide a means to overcome the Shockley-Queisser limit in photovoltaics. SF as measured by the decay of S has been shown to occur efficiently and independently of temperature, even when the energy of S is as much as 200 meV less than that of 2T. Here we study films of triisopropylsilyltetracene using transient optical spectroscopy and show that the triplet pair state (TT), which has been prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
366
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 213 publications
(404 citation statements)
references
References 39 publications
33
366
5
Order By: Relevance
“…In keeping with previous assignments, the first spectral peaks at 560 nm are attributed to 0-0, i.e. zerophonon, transitions [22]. This is also consistent with the greater overlap of low-energy modes on the higherorder vibrational transitions described in detail below (Fig.…”
Section: Spectrally Resolving Interacting Tripletssupporting
confidence: 90%
“…In keeping with previous assignments, the first spectral peaks at 560 nm are attributed to 0-0, i.e. zerophonon, transitions [22]. This is also consistent with the greater overlap of low-energy modes on the higherorder vibrational transitions described in detail below (Fig.…”
Section: Spectrally Resolving Interacting Tripletssupporting
confidence: 90%
“…Transient absorption spectroscopy (solid line) has shown that triplet photoinduced absorption signatures generated by singlet fission occur well within our instrument response and do not decay significantly until >10µs 44 . The same sample shows emission with 10ns lifetime, attributed to delayed fluorescence during the S1-1 (TT) equilibrium 44 . This decay closely matches our prompt emission decay (open circles).…”
Section: Diketopyrrolopyrrole Thiophene (Dpptmentioning
confidence: 82%
“…This is a critical distinction from inorganic excitonpolaritons that has not yet been addressed in the literature. The existence of this state mixing is a critical driver in photophysical processes such as ultrafast intersystem crossing 45 , thermally activated delayed fluorescence 46 , singlet exciton fission 42,44 and its reverse, triplet-triplet annihilation. For example, in singlet fission the nominal S1 state contains both CT and TT character, in some cases such as pentacene films to a surprisingly high degree (circa 50% CT) 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In synthetic molecular materials developed for organic electronics they have transformed transistor and lightemitting diode technology [6][7][8] , as well as becoming promising components for next-generation photovoltaic (PV) devices with the potential to overcome the Shockley-Queisser limit via singlet fission (SF). In SF the absorption of a single photon ideally results in the formation of two spatially separated triplet excitons [9][10][11][12] , although a concerted sequence of ultrafast electronic and vibrational dynamics must compete with both radiative and non-radiative losses for this exciton multiplication to be efficient enough for applications [13][14][15][16][17] . Observation, understanding and control of these many-body quantum dynamics is therefore essential for optimisation of conjugated molecules for technologies such as SFenhanced PVs [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%